The ability of people with intellectual disability to use inhalers – an exploratory mixed methods study. (2nd January 2016) - Davis, Sharon; Durvasula, Seeta; Merhi, Diana; Young, Paul; Traini, Daniela; Bosnic-Anticevich, Sinthia
Abstract: Objective : This aim of this study was to assess inhaler technique of people with intellectual disability (ID), and evaluate the effectiveness of teaching with respect to their individual ability to adopt correct technique. Methods : Seventeen people with ID were recruited through existing networks of general practitioners and disability support organisations. Inhaler technique was assessed using validated checklists and placebo devices, followed by provision of individualised training. The educational interaction between participant and researcher was captured via video recording and analysed qualitatively. Results : Seventeen people with ID participated; females comprised 65%. At baseline, no participants correctly used any device. Pressurised metered dose inhalers, with or without accessory devices, were the most poorly used devices. Inhalation steps were poorly performed across all devices. Following training, the proportions of assessed participants that were able to master inhaler technique were 100% of Accuhaler users, 40% of Turbuhaler users, 25% of pressurised metered dose inhaler users and 0% of Handihaler users. Barriers identified included poor comprehension of breathing processes, the lack of attentiveness and poor dexterity. Facilitators for educator delivery of inhaler technique education included the use of analogies and being patient. Conclusions : This is the first study to examine inhaler technique mastery in people with ID. Results show that with education that addresses the unique patient barriers inherent in this group, some individuals can be trained to mastery. Structured modules of inhaler technique training tailored for people with ID, but which can be individualised, are recommended.